Marketing Strategy of Bvlgari - Mursalova, Leyli; Halík, Jaroslav, 1961-; Šípková, Martina; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2023)
My thesis is focused on analyzing the marketing strategy of “Bulgari.” The thesis is divided into theoretical and practical (analytical) sections. The first section outlines the theoretical methods that are advised for use in creating a marketing plan. The practical part will concentrate on choosing the best marketing plan for a product launch that the business should employ. This thesis will be based on primary and desk research regarding the current market size, competitors, and most recent market trends. The aim of my thesis is to describe the ways of marketing improvement of the company “Bulgari,” thus revealing their advantages and disadvantages in order to make a proper choice.
Vedoucí práce: Jaroslav Halík
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2023
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2023
Způsob přístupu: Internet
Keywords: international business [obor bakal. práce]; bakalářské práce; bachelor's theses